Site-specific interactions enhanced dissolution of natural aragonite (110) surfaces in succinic acid (SUC) solutions: Implications for the oceanic aragonite dissolution fluxes. (15th February 2022) - Tang, Hongmei; Wu, Xiao; Yang, Yiping; Xian, Haiyang; Zhu, Jianxi; Fan, Min; Xi, Xiping; Wei, Jingming; Du, Runxiang; Liu, Hongmei; Zhu, Runliang
Abstract: Aragonite, one of the most common biological calcium carbonate minerals, is widespread in marine plankton and neritic sediments (e.g., accounting for 89% of pelagic calcification of CaCO3 in the surface ocean). Its dissolution directly affects the export fluxes of CaCO3 in seawater. The aragonite dissolution in the ocean correlates with the increase of partial pressure of carbon dioxide and is pertinent to acidic biomolecules. However, aragonite dissolution in seawater with acidic biomolecules has been overlooked, and the interaction mechanism is unclear. In-situ atomic force microscopy (AFM) was employed to observe the dissolution features of aragonite (110) growth surfaces in succinic acid (SUC, HOOC-CH2 -CH2 -COOH) solutions. The results demonstrate that (1) both the morphologies and spreading rates of the etch pits formed on aragonite (110) surfaces are altered by the interactions between SUC molecules and the surfaces; (2) the [1 1 ‾ 1] and [ 1 ‾ 11] steps of the etch pits on aragonite (110) surfaces in SUC solutions are kinetically controlled; (3) dissolution rates of aragonite (110) surfaces are proportional to SUC concentrations, which is attributed to the strong complexation between SUC molecules and surface-bounded Ca atoms ( ≡ C a + ); (4) etch pits morphologies of aragonite (110) and calcite (10.4) surfaces are different in SUC solutions, and the spreading rates of the etch pits of the former are one to two orders of magnitude lower than those of the latter. Furthermore, aragonite is found to be more sensitive to SUC molecules than calcite, suggesting that dissolving aragonitic materials could be more easily affected by circumambient biomolecules than dissolving calcitic materials. In seawater that contains organic molecules, the dissolution fluxes of aragonite could be much slower than those of calcite. These findings not only reveal the site-specific interactions between SUC molecules and the ≡ C a + on aragonite (110) surfaces but also emphasize its implication for the oceanic aragonite dissolution fluxes.